PENGGANDAAN SKALA PRODUKSI ENZIM GLUKOAMILASE DARI LABU KOCOK KE FERMENTOR 10 L - Patuan L. P. Siagian; A. T. Karossi; Yetti M.lskandar; Tigor N. Surawidjaja; Ngadiman Ngadiman (Research Center for Chemistry - LIPI, 1994)
Glucoamylase was produced in a 10 L stirred tank fermentor using Rhizopus oryzae L16 and sago (Metroxylon spy starch. Fermentation conditions were adapted from the results obtained from shake flask (250 mL) and 4L fermentor experiments. At the present investigation, the temperature was set at 30°C, pHs were at a constant value of 4.0, 4.5, 5.0, 5.5, and 6.0. Agitation rate at aeration 1.5 vvm were adjusted to 286 rpm, 300 rpm, and 350 rpm (medium volume 6 L). The maximum production of glucoamylase was reached at agitation rate 350 rpm, aeration 1.5 wm and pH 4.0. At day-s, the glucoamylase activity was 2,285 U/L and its specific activity was 9,326 U/g protein. At day-5 the specific activity increased to 13,631 U/g protein. This maximum production was reached at an average kLa of43 h(-1)